2014
DOI: 10.2106/jbjs.l.00008
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Efficacy of Antifibrinolytics in Adolescent Idiopathic Scoliosis

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 24 publications
3
60
0
2
Order By: Relevance
“…Multiple studies have demonstrated the potential effectiveness of intraoperative antifibrinolytic therapy in significantly reducing blood loss (A. Soroceanu et al, unpublished data). 9,36,65 In addition, a recently published application of rotational thromboelastometry-guided blood product management to major spine procedures suggests that this technology may aid in reducing blood loss, blood product use, and cost. 31 Infections accounted for 9% of all major complications, and deep wound infection was the most common infection.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated the potential effectiveness of intraoperative antifibrinolytic therapy in significantly reducing blood loss (A. Soroceanu et al, unpublished data). 9,36,65 In addition, a recently published application of rotational thromboelastometry-guided blood product management to major spine procedures suggests that this technology may aid in reducing blood loss, blood product use, and cost. 31 Infections accounted for 9% of all major complications, and deep wound infection was the most common infection.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a benefit to reducing operative blood loss in order to reduce postoperative LOS. Several methods of reducing intraoperative blood loss show promise, including, tranexamic acid [26,47,53], use of a bipolar sealer [15,28], and intrathecal morphine [23]. While minimally invasive procedures have been reported to reduce postoperative LOS and blood loss in patients treated with other spinal procedures [10,36,40,48], minimally invasive surgery for AIS has not yet shown the same benefits [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, anti-fibrinolytic agents such as Transexamic Acid (TXA) and aminocaproic acid have been shown to decrease intraoperative blood loss and transfusion rates, as evidenced by recent systematic reviews and meta-analysis studies [17][18][19]. Most of the studies have been small, single-center and prospective or retrospective in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies have been small, single-center and prospective or retrospective in nature. Recently, a prospective randomized trial involving 125 patients with AIS showed that both TXA and aminocaproic acid reduced intraoperative blood loss when compared with saline solution [19], although they did not find a decrease in transfusion rates. However, in the Jehovah's Witness population where transfusion is not an option, reducing intraoperative blood loss is the primary goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation